Biomassa e perfil metabólico microbiano em solos sobre sistemas de produção integrados no estado de Mato Grosso - Okada, Antonio Shoity (2019)
The different arrangements that make up the integrated production systems added to the environmental conditions are factors that interfere with the soil ecosystem. The objective of this study was to evaluate if the metabolic profile (PM) and the amount of soil microbial biomass carbon (CBM) are modulated by the use of integrated and exclusive production systems in the State of Mato Grosso. Soil samples were collected in March 2016 during the rainy season. Three monoculture systems (Eucalyptus (F), Lavoura (L) and Pasture (P)) and seven integrated systems (IL-P, IP -L, ILF, IPF, ILF-IPF, IPF-ILF, ILPF) arranged in four randomized blocks, in addition to the reference areas, native forest and fallow. ECOPLATE® microplates (Biolog) were used to determine PM and the CBM content was analyzed by fumigation extraction and total organic carbon analyzer (various TOC cube). The highest CBM content was observed in the Pasture (310.09 mg C kg-1), and the lowest biomass carbon content was observed in the Forest (124.26 mg C kg-1) and the native forest reference area (270.45 mg C kg-1). In the evaluation of the metabolic profile, it was possible to observe the formation of the different groups of microorganisms separated according to the metabolic profile in the integrated and exclusive systems. Therefore, with these results we can observe that the metabolic profile and the carbon of the microbial biomass, demonstrated that they can be modulated by different integrated and exclusive systems of production, serving as sensitive bioindicators, allowing to detect alterations in the microbial communities of the soil on the effects of the management and anthropic influence on the soil.